Universal Line-Sets for Drawing Planar 3-Trees - Hossain, Md. Iqbal; Mondal, Debajyoti; Rahman, Md. Saidur; Salma, Sammi Abida (Journal of Graph Algorithms and Applications, 2013)
A set S of lines is universal for drawing planar graphs with n vertices if every planar graph G with n vertices can be drawn on S such that each vertex of G is drawn as a point on a line of S and each edge is drawn as a straight-line segment without any edge crossing. It is known that ⎣[(2(n−1))/3]⎦ parallel lines are universal for any planar graph with n vertices. In this paper we show that a set of ⎣[(n+3)/2]⎦ parallel lines or a set of ⎡[(n+3)/4]⎤ concentric circles are universal for drawing planar 3-trees with n vertices. In both cases we give linear-time algorithms to find such drawings. A by-product of our algorithm is the generalization of the known bijection between plane 3-trees and rooted full ternary trees to the bijection between planar 3-trees and unrooted full ternary trees. We also identify some subclasses of planar 3-trees whose drawings are supported by fewer than ⎣[(n+3)/2]⎦ parallel lines.